EXPLORATING THE ESSENTIALS OF JOB ATTITUDES' AND PSYCHOLOGICAL CAPITAL FOR THEIR HEALTH PROFESSIONALS' PERFORMANCE IN PUBLIC SECTOR HOSPITALS - Marzuki (Universitas Efarina, 2022)
The concept of job attitudes and psychological capital, their role in performance in the context of hospital organizations is very important. There is still a dearth of research developing the model in its entirety. The purpose of this research is to develop a model of the essentials of job attitudes and psychological capital on the performance of health professionals in the context of hospital organizations and to try to develop a model empirical research. Various approaches and tools are used in the framework, which presents a review that provides high-level views and various perspectives and interactions from the essence of job attitudes' and psychological capital constructs in other workplaces starting with a review of the concept of job attitudes' and psychological capital construction in the context of hospital organizations. , then its role on the performance of Health Professionals. The results of this study developed a model, the essentials of job attitudes and psychological capital on the performance of health professionals in the context of hospital organizations and an empirical research model. Organizations can influence work performance on organizational mechanisms, and individual mechanisms to achieve effective and efficient transformation and improvement of health professionals' performance.